STUDI IMPLEMENTASI KONSEP RUANG HETEROTOPIA PADA INTERIOR GEREJA KATOLIK TRITUNGGAL MAHAKUDUS TUKA-DALUNG BALI - Sitinjak, Ronald H. Irianto; Jong, Sherly de (Institute of Research and Community Outreach - Petra Christian University, 2007)
Heterotopias space, according to Michel Foucoult, is an unrealistic space or dimension in a realistic one. These sites are very dynamic and can be changed by even the smallest turn of events or time. Some of these changes vary from mild-changes to, what was called by Foucault, counter-sites, a site with two very measurable differences of activities, even the exact opposite activities e.g. real sites to unreal sites and sacred sites to profane sites. This phenomen was found, unexpectedly, in a Catholic Church, Tritunggal Mahakudus in Tuka-Dalung Bali, a building generally known by its high sanctity. A phenomenon that was thought unlikely to be found in a church, especially a Catholic Church, was made possible by cultural changes, one form of Catholic's enculturation movement, and the shifting of time or activity. The main cause of these so called phenomena is the presence and the opening and closing of a gedong's door, a traditional Balinese room usually used in traditional Balinese houses and temples for storing and holding religious and sacred items. These adapted gedong was first used as a Balinese cultural representation in a western-based church, but in practice it serves more purposes than just that. It serves both as the connector and the divider of sanctity of a room. Furthermore, it also became a prominent being of changing situation and activity (from sacred to profane and vice versa) thus becoming a heterotopias room. One of it factors is the placement of these partition wall between sacred area and profane area during different activities. Abstract ini Bahasa Indonesia : Ruang heterotopia menurut Michel Foucault adalah dimensi atau ruang tidak nyata dalam ruang nyata. Dimensi tidak nyata ini relatif dan bisa bergeser. Pergeseran dimensi yang relatif ini bisa terjadi dari pergeseran karakter-karakter ruang yang saling bertentangan, misalnya dari ruang yang nyata ke tidak nyata, ruang sakral ke profan. Fenomena ini, secara tak terduga, juga terjadi di dalam sebuah bangunan gereja Katolik, yang biasanya terkenal dengan kesakralannya yang tinggi. Fenomena ruang heterotopia pada Gereja Katolik Tritunggal Mahakudus (TMK) Tuka-Dalung Bali ini terjadi oleh pergeseran dimensi budaya, sebagai salah satu wujud inkulturasi budaya lokal, dan waktu atau aktivitas. Fenomena ini ditandai dengan terbuka dan tertutupnya pintu gedong, sebuah ruang tradisional Bali yang digunakan untuk menyimpan benda-benda keagamaan dan suci, pada gereja ini. Gedong yang semula ada sebagai perwujudan adopsi budaya lokal pada gereja TMK, dalam prakteknya memiliki fungsi yang lebih, yaitu sebagai penghubung dan pemisah kesakralan sebuah ruangan, sebagai penanda terjadinya perubahan aktivitas (sakral ke profan dan sebaliknya) dan membentuk ruang heterotopia. Salah satu faktor pendukungnya adalah terjadinya pergeseran dinding pembatas area sakral dan profan saat terjadinya perubahan aktivitas. Kata kunci: Ruang, Heterotopia, Interior, Gereja Katolik, Tuka Dalung, Bali.